Students’ perceptions of the utility of pedagogical approaches used by lecturers in selected faculties at a Zimbabwean University. - Maphosa, Cosmas; Zikhali, Joyce; Chauraya, Efiritha; Madzanire, Daniel (Kamla-Raj, 2016)
This study sought to establish students’ perceptions of the usefulness of teaching approaches employed by lecturers in one university in Zimbabwe. The study was informed by the constructivist theory of learning. The study adopted a descriptive survey approach which utilized both qualitative and quantitative methodologies. Data were collected from students in five Faculties in the selected university. A random sample of one hundred and ten students, comprising of sixty-five male and forty-five female students participated in the study. A semi-structured questionnaire was used to collect both quantitative and qualitative data. Quantitative data were analysed with the aid of the SPSS statistical software package version 21. Qualitative data were analysed u sing content analysis method and presented through verbatim quotations of the respondents. The study found that students held different perceptions on what they deemed effective teaching approaches. The study concludes that exposure to traditional approaches to teaching made students view them as effective. Recommendations were made that a shift from traditional lecture approaches would ensure the use of more student-centered approaches.